2016
DOI: 10.1016/j.toxicon.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Algal toxin profiles in Nigerian coastal waters (Gulf of Guinea) using passive sampling and liquid chromatography coupled to mass spectrometry

Abstract: Algal toxins may accumulate in fish and shellfish and thus cause poisoning in consumers of seafood. Such toxins and the algae producing them are regularly surveyed in many countries, including Europe, North America, Japan and others. However, very little is known regards the occurrence of such algae and their toxins in most African countries. This paper reports on a survey of phytoplankton and algal toxins in Nigerian coastal waters. Seawater samples were obtained from four sites for phytoplankton identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…This may not be unconnected with the higher prevalence of toxin-producing species generally observed in the SW in contrast to the SS locations . Earlier study by Zendong et al (2016) recorded substantial quantities of specific marine algal biotoxins in SW Lekki and Bar beach relative to SS Rivers and Akwa Ibom. The SW coastal Nigeria is reckoned to be of more elevated salinity than the SS (Zendong et al, 2016) with greater preponderance for toxic dinoflagellates to survive (Delmas et al, 1992;Zendong et al, 2016) whereas the salinity of SS is diluted by the Niger delta inflows.…”
Section: Discussionmentioning
confidence: 95%
“…This may not be unconnected with the higher prevalence of toxin-producing species generally observed in the SW in contrast to the SS locations . Earlier study by Zendong et al (2016) recorded substantial quantities of specific marine algal biotoxins in SW Lekki and Bar beach relative to SS Rivers and Akwa Ibom. The SW coastal Nigeria is reckoned to be of more elevated salinity than the SS (Zendong et al, 2016) with greater preponderance for toxic dinoflagellates to survive (Delmas et al, 1992;Zendong et al, 2016) whereas the salinity of SS is diluted by the Niger delta inflows.…”
Section: Discussionmentioning
confidence: 95%
“…OA, DTX-1, PTX-2, PTX-2sa and 7-epi-PTX-2sa were detected in the Yellow Sea in China (maximum 165, 56, 107 and 50 ng/g HP20 resin for OA, DTX-1, PTX-2 and PTX2-sa + 7-epi-PTX-2sa, respectively) [ 49 , 52 ]. Finally, OA, DTX1, PTX2 and PTX2sa were detected in Nigerian coastal waters of Africa (Atlantic Ocean) (60 ng OA/g HP20 resin) [ 42 ] and in French coastal areas of the Mediterranean Sea (650, 120, 500, 100 ng/g HP20 resin, respectively) and Atlantic Ocean (130, 3, 1800, 160 ng/g HP20 resin, respectively) [ 23 ], where results also showed that toxin concentrations and profiles in SPATTs were dependent on the amount of resin used (0.3, 3, and 10 g of HP20 resin) and that SPATTs bags containing 3 g of resin appeared to be the best compromise.…”
Section: Application Of Spatt Technology For the Monitoring Of Aqumentioning
confidence: 99%
“…To date, there is no general consensus in the literature about the optimal deployment time for SPATT devices in the field. In fact, passive samplers were generally deployed on a weekly basis [ 21 , 31 , 35 , 40 , 42 , 46 , 50 , 51 , 58 ], but sometimes, the time of deployment was reduced to few hours [ 32 , 37 , 47 , 52 , 53 ] or extended to a month [ 34 , 41 , 43 , 44 , 49 ]. So, the deployment duration varies and generally depends on the research or monitoring program design (e.g., short- or long-term monitoring, adsorbent substrate used, toxin targeted, …) together with the feasibility on the field (e.g., duration of the field mission, accessibility of the monitored area, hydrodynamism of the monitored area, …) [ 25 ].…”
Section: Implications In Terms Of Monitoring Of Emerging Toxic Rismentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier preliminary reports by [21] [22] [23] [24] revealed the presence of potentially toxic phytoplankton in the Nigerian coastal waters. More recently, Zendong et al [25] reported the presence of algal toxin in the coastal waters of Nigeria. Although there are no records of human illness and massive aquatic animals and fish kills in Nigerian coastal waters, the presence of toxins producing species of phytoplankton implies the possibilities of its occurrence.…”
Section: Introductionmentioning
confidence: 99%